Síntese de análogos de 3-O-(undec-10-en-1-il)- D-glicose e investigação de sua atividade antiplasmodial - Marilda Pereira Lisboa (2007)
3-O-alkyl-D-glucose derivatives, mainly 3-O-undecenyl-D-glucose, display antiplasmodial activity due inhibition of the Plasmodium falciparum hexose transporter (PfHT1). Specifically, the inhibition of this transporter blocks the glucose flowing, and consequently, the parasite dies because of the lack of nourishment. Based on this observation, 3-Oundecenyl- D-glucose analogs were designed, synthesized and their antiplasmodial activity was evaluated. To obtain these derivatives, D-glucose was protected at positions 1, 2 and 5, 6, in a reaction carried out in dry acetone, sulfuric acid and copper sulfate. The resultingproduct, a diacetonide, was submitted to alkylation reactions in phase transfer catalysis conditions with distinct halides and mesylates. Phase transfer reaction conditions were diethyl ether, aqueous sodium hydroxide 50% and tetrabutylammonium bromide. To afford theprotected products, halides and mesylates not available commercially were synthesized, and then, used in the alkylation reactions. Deprotection of these compounds was achieved under acidic conditions using Amberlite IRA-120 resin as the catalyst. Antiplasmodial activity ofthe synthesized D-glucose derivatives was investigated employing Plasmodium falciparum W2 strain, which is chloroquine resistant, in assays based on [3H]-hypoxanthine uptake. Among evaluated compounds, 3-O-benzyl-D-glucose and 3-O-[3-(p-alyloxiphenyl)-n-propyl]-D-glucose showed activity of 21 ìM e 37 ìM, respectively. The lead compound, 3-Oundecenyl- D-glucose, was not active under the experimental conditions employed. Keywords: Malaria; inhibitors; D-glicose analogues; organic synthesis.